Low-frequency electronic noise in superlattice and random-packed thin films of colloidal quantum dots. Issue 42 (16th October 2019) - Geremew, Adane; Qian, Caroline; Abelson, Alex; Rumyantsev, Sergey; Kargar, Fariborz; Law, Matt; Balandin, Alexander A.
Abstract : We report measurements of low-frequency electronic noise in ordered superlattice, weakly-ordered and random-packed thin films of 6.5 nm PbSe quantum dots prepared using several different ligand chemistries. Abstract : We report measurements of low-frequency electronic noise in ordered superlattice, weakly-ordered and random-packed thin films of 6.5 nm PbSe quantum dots prepared using several different ligand chemistries. For all samples, the normalized noise spectral density of the dark current revealed a Lorentzian component, reminiscent of the generation–recombination noise, superimposed on the 1/ f background ( f is the frequency). An activation energy of ∼0.3 eV was extracted from the temperature dependence of the noise spectra in the ordered and random quantum dot films. The noise level in the ordered films was lower than that in the weakly-ordered and random-packed films. A large variation in the magnitude of the noise spectral density was also observed in samples with different ligand treatments. The obtained results are important for application of colloidal quantum dot films in photodetectors.